2008
DOI: 10.1038/nature07333
|View full text |Cite
|
Sign up to set email alerts
|

Central role of detachment faults in accretion of slow-spreading oceanic lithosphere

Abstract: Enhanced seismicity is probably generated along detachment faults accommodating a sizeable proportion of the total plate separation. In contrast, symmetrical segments have lower levels of seismicity, which concentrates primarily at their ends. Basalts erupted along asymmetrical segments have compositions that are consistent with crystallization at higher pressures than basalts from symmetrical segments, and with lower extents of partial melting of the mantle. The large fields of detachment surfaces recently id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
382
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(406 citation statements)
references
References 37 publications
17
382
1
6
Order By: Relevance
“…Type 3 is the most recently identified, from the Lost City site, 30°N MAR (10) and also involves serpentinization of ultramafic rock but yielding substantially lower fluid temperatures exiting the sea floor (∼40-90°C). The Lost City style of venting is associated with long-lived detachment surfaces that play an important role in extension along all slow spreading ridges (22). Although plume data for Lost City are not available, the vent fluids contain CH 4 and H 2 at levels comparable to Type 2 vents but with much lower dissolved metal concentrations (10,23).…”
mentioning
confidence: 99%
“…Type 3 is the most recently identified, from the Lost City site, 30°N MAR (10) and also involves serpentinization of ultramafic rock but yielding substantially lower fluid temperatures exiting the sea floor (∼40-90°C). The Lost City style of venting is associated with long-lived detachment surfaces that play an important role in extension along all slow spreading ridges (22). Although plume data for Lost City are not available, the vent fluids contain CH 4 and H 2 at levels comparable to Type 2 vents but with much lower dissolved metal concentrations (10,23).…”
mentioning
confidence: 99%
“…[2] Oceanic core complexes (OCCs), are widespread features along the mid-Atlantic Ridge and other slow and ultra-slow spreading ridges [e.g., Escartín et al, 2008;Tucholke et al, 2008], where they are involved in the accretion of large areas of the seafloor [Smith et al, 2006;Cannat et al, 2006]. The low-angle detachment faults exposed at the seafloor unroof and expose sections of lower crust and mantle, accommodating elevated strains over long periods of time, sometimes in excess of 1 Myrs, possibly promoting serpentinization within these structures.…”
Section: Introductionmentioning
confidence: 99%
“…Oceanic core complexes now appear to be common along slow-and ultraslow-spreading ridges such as the MAR and SWIR. Indeed, Escartin et al (2008) suggested that detachment faulting and oceanic core complexes occur along almost half the MAR between 12 30 0 N and 35 N.…”
mentioning
confidence: 99%